2011
DOI: 10.1177/003335491112600108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Health-Risk Behaviors among Asian American and Pacific Islander High School Students in the U.S., 2001–2007

Abstract: The prevalence estimates of health-risk behaviors exhibited by Asian American students and Pacific Islander students are very different and should be reported separately whenever feasible. To address the different health-risk behaviors exhibited by Asian American and Pacific Islander students, prevention programs should use culturally sensitive strategies and materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Data from a national adolescent sample collected between 2001 and 2007 revealed that male and female Pacific Islander high school students were second only to white students in terms of current tobacco use prevalence ©SAGE Publications at 24.8% and 26.5%, respectively. Pacific Islander females at 25.8% had higher rates of past month smoking than Pacific Islander males at 23.7% (Lowry, Eaton, Brener, & Kann, 2011). The elevated rates of tobacco use among Pacific Islander girls and women are particularly disconcerting.…”
Section: Substance Usementioning
confidence: 90%
“…Data from a national adolescent sample collected between 2001 and 2007 revealed that male and female Pacific Islander high school students were second only to white students in terms of current tobacco use prevalence ©SAGE Publications at 24.8% and 26.5%, respectively. Pacific Islander females at 25.8% had higher rates of past month smoking than Pacific Islander males at 23.7% (Lowry, Eaton, Brener, & Kann, 2011). The elevated rates of tobacco use among Pacific Islander girls and women are particularly disconcerting.…”
Section: Substance Usementioning
confidence: 90%
“…In the TEDS, amphetamines and marijuana were the most commonly identified classes of abused drugs for female Asian-Americans/NHs/PIs (23%, 19% respectively) and male Asian-Americans/NHs/PIs (17%, 21% respectively) (SAMHSA, 2012). While research tends to show a low prevalence of substance use in the pooled sample, analyses that specifically examine NHs/PIs find a higher prevalence of substance use and delinquency among NHs/PIs than among Asian-Americans (Andrade et al, 2006; Lowry et al 2011; Wu et al 2013c). Thus, it is important to examine Asian-Americans and NHs/PIs separately for NMSU.…”
Section: Introductionmentioning
confidence: 92%
“…The proportion of adolescents who reported ever having sexual intercourse was nearly 12% of East Asian students (i.e., Chinese, Korean, and Japanese) in grades 7 to 12 in the 2003 British Columbia Adolescent Health Survey , and about 20% of Japanese American adolescents in grades 9 to 12 in the 2003 Hawaii Youth Risk Behavior Survey (Sasaki & Kameoka). Nevertheless, among sexually experienced adolescents, the prevalence of high risk sexual behaviours among those who are Asians did not differ from that of their peers (Grunbaum et al;Hou & Basen-Engquist, 1997;Lowry et al;.…”
Section: Introductionmentioning
confidence: 95%
“…In North America, Asian adolescents are less likely to be sexually experienced than adolescents from other ethnic groups (Grunbaum, Lowry, Kann, & Pateman, 2000;Kuo & St Lawrence, 2006;Lowry, Eaton, Brener, & Kann, 2011;Sasaki & Kameoka, 2009;Spence & Brewster, 2010). The proportion of adolescents who reported ever having sexual intercourse was nearly 12% of East Asian students (i.e., Chinese, Korean, and Japanese) in grades 7 to 12 in the 2003 British Columbia Adolescent Health Survey , and about 20% of Japanese American adolescents in grades 9 to 12 in the 2003 Hawaii Youth Risk Behavior Survey (Sasaki & Kameoka).…”
Section: Introductionmentioning
confidence: 99%